2022
DOI: 10.1093/conphys/coac008
|View full text |Cite
|
Sign up to set email alerts
|

Towards the integration of ecophysiology with fisheries stock assessment for conservation policy and evaluating the status of the Mediterranean Sea

Abstract: Recent European Union (EU) regulations have been introduced to discourage the capture of undersized specimens with the aim of reducing the bycatch mortality imposed by commercial fisheries. We argue that we still lack accurate data regarding basic information required to properly implement these regulations for most Mediterranean ecosystems, including the true mortality imposed by fisheries, escape rates from fishing gears and the capability of specimens to survive following discard. We suggest that additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The low commercial value of dogfish compared to other demersal species it in the Mediterranean Sea (Ragonese et al, 2013) commonly results in only specimens larger than 36 cm total body length (TL) being retained for human consumption, while all specimens <36 cm TL are discarded back to the sea (Abella and Serena, 2005) because it is estimated that Scyliorhinus caniculas could reach the first maturity after that body size (Bendiab et al, 2012). Many individuals that are discarded or incidentally captured (i.e., bycatch) are either already dead, experience post-release mortality, or suffer detrimental long-term sub-lethal effects as reported by (Falco et al, 2022). Dogfish are commonly captured with bottom trawl fishing gear off the coast of Sicily (Falco et al, 2022;Peristeraki et al, 2020;Ragonese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low commercial value of dogfish compared to other demersal species it in the Mediterranean Sea (Ragonese et al, 2013) commonly results in only specimens larger than 36 cm total body length (TL) being retained for human consumption, while all specimens <36 cm TL are discarded back to the sea (Abella and Serena, 2005) because it is estimated that Scyliorhinus caniculas could reach the first maturity after that body size (Bendiab et al, 2012). Many individuals that are discarded or incidentally captured (i.e., bycatch) are either already dead, experience post-release mortality, or suffer detrimental long-term sub-lethal effects as reported by (Falco et al, 2022). Dogfish are commonly captured with bottom trawl fishing gear off the coast of Sicily (Falco et al, 2022;Peristeraki et al, 2020;Ragonese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals that are discarded or incidentally captured (i.e., bycatch) are either already dead, experience post-release mortality, or suffer detrimental long-term sub-lethal effects as reported by (Falco et al, 2022). Dogfish are commonly captured with bottom trawl fishing gear off the coast of Sicily (Falco et al, 2022;Peristeraki et al, 2020;Ragonese et al, 2013). This fishing gear can subject the captured dogfish to cumulative physical trauma and physiological stress through: a) prolonged exposure (e.g., in excess of 60 mins) to compression from all the biomass accumulated in the cod end of the net with additional potential exposure to dangerous items (such as solid litter including metals); b) repeated attempts to escape through the mesh of the cod end of the net; c) marked changes to ambient temperatures, salinity and light intensity as the gear ascends from the deep waters to the surface; d) exposure on the deck of the boat to air and direct sunlight for extended periods of time; e) handling operations by the crew; f) exposure to different ambient conditions following discard back to the sea; and, finally, g) release into a new location that may not be as favorable to the dogfish as the original location of capture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, as previous research had indicated, discarding plaice that have gone through a commercial beam-trawl capture event in summer is likely to be fatal ( Uhlmann et al., 2016 , 2021 , 2023 ). Accordingly, it can be sensible to grant an actionable exemption in those seasons and regions when release survival can be maximized and routinely collect vitality-relevant parameters during at-sea monitoring campaigns ( Falco et al., 2022 ). It is likely that under current climate change scenarios, warming seawater temperatures will only further compromise the reasoning behind the existing high survival exemption for plaice.…”
Section: Discussionmentioning
confidence: 99%
“…For commercial fisheries, individuals are commonly discarded if they are non-target species or unable to be retained due to legislation (e.g. they are of a non-legal size or are out of season ( Falco et al, 2022 )). In the case of recreational fishing, ‘catch-and-release’ angling is often performed as a conservation strategy, with the assumption that fish can generally recover and survive after being returned to their natural environment after capture ( Arlinghaus et al, 2007 ; Cooke and Schramm, 2007 ).…”
Section: Introductionmentioning
confidence: 99%